Correlating Infant Fecal Microbiota Composition and Human Milk Oligosaccharide Consumption by Microbiota of 1‐Month‐Old Breastfed Infants. Issue 13 (30th April 2019) - Borewicz, Klaudyna; Gu, Fangjie; Saccenti, Edoardo; Arts, Ilja C.W.; Penders, John; Thijs, Carel; van Leeuwen, Sander S.; Lindner, Cordula; Nauta, Arjen; van Leusen, Ellen; Schols, Henk A.; Smidt, Hauke
Abstract : Scope: Understanding the biological functions of human milk oligosaccharides (HMOs) in shaping gastrointestinal (GI) tract microbiota during infancy is of great interest. A link between HMOs in maternal milk and infant fecal microbiota composition is examined and the role of microbiota in degrading HMOs within the GI tract of healthy, breastfed, 1‐month‐old infants is investigated. Methods and results: Maternal breast milk and infant feces are from the KOALA Birth Cohort. HMOs are quantified in milk and infant fecal samples using liquid chromatography‐mass spectrometry. Fecal microbiota composition is characterized using Illumina HiSeq 16S rRNA gene amplicon sequencing. The composition is associated with gender, delivery mode, and milk HMOs: Lacto‐ N ‐fucopentaose I and 2′‐fucosyllactose. Overall, Bifidobacterium, Bacteroides, Escherichia–Shigella, and Parabacteroides are predominating genera. Three different patterns in infant fecal microbiota structure are detected. GI degradation of HMOs is strongly associated with fecal microbiota composition, and there is a link between utilization of specific HMOs and relative abundance of various phylotypes (operational taxonomic units). Conclusions: HMOs in maternal milk are among the important factors shaping GI tract microbiota in 1‐month‐old breastfed infants. An infant's ability to metabolize different HMOs strongly correlates with fecal microbiota composition and specifically with phylotypes within genera Bifidobacterium, Bacteroides, and Lactobacillus . Abstract : The role of microbiota in degrading human milk oligosaccharides (HMOs) within the gastrointestinal (GI) tract of healthy, breastfed, 1‐month‐old infants is investigated. Degradation of HMOs and microbiota composition are associated with gender and mode of delivery and differ between specific HMOs. Three different clusters are detected in the infant fecal microbiota structure.